E-010 Triple coaxial catheter technique for coil embolization of cerebral aneurysms. (16th November 2010) - Uemura, A; Fujii, M; Yamamoto, D; Matsukawa, H; Kobayashi, N; Numaguchi, Y
Abstract : Introduction: Keeping microcatheters stable in anterior cerebral artery (ACA) or middle cerebral artery (MCA) aneurysms during coil embolization is crucial in the success of the treatment. We currently use a triple coaxial catheter system by using long 4 French or 5 French Cerulean G catheters (Medikit, Tokyo, Japan) as second guiding catheter to support microcatheters in cases of distal cerebral aneurysms. The purpose of this retrospective study is to evaluate the efficacy of the triple coaxial system in the treatment of distal cerebral aneurysms. Materials and methods: We retrospectively reviewed eight cases (five men and three women; aged 47–90 years; mean 68.1 years) of ACA and MCA ruptured aneurysms treated by endovascular coil embolization by using the triple coaxial system between April 2009 and February 2010. The location of the aneurysms included the anterior communicating artery (n=6), distal ACA (n=1) and distal MCA (n=1). A 5 French guiding sheath (n=4) or 6 French guiding catheter (n=4) was used as the primary guiding catheter. A 4 French or 5 French Cerulean G catheter was introduced up to the petrous portion of the internal carotid artery as a second guiding catheter. Evaluated subjects included success of microcatheter navigation, stability of microcatheter during the procedure and other technical issues. Results: In all cases, a microcatheter was navigated into the aneurysms successfully. Microcatheters were kept stable inside the aneurysms during the procedure. However, to advance preshaped SL-10 microcatheters (Boston Scientific, Natick, Massachusetts, USA) inside 4 French Cerulean G catheter in two cases was so difficult that we had to exchange the microcatheter to another one. There was no complication associated with the technique. Contrast injection through the guiding catheter during the procedure was slightly hard when 6 French guiding catheters were used as the primary guiding catheter. Conclusion: Triple coaxial system for ACA and MCA aneurysms is a safe and feasible technique. However there are several technical issues that we have to take into account.